Penerapan Model Pembelajaran Discovery Learning untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Pemeliharaan Kelistrikan Kendaraan Ringan di SMK YPT Purworejo (Lembag, 2026)
This study aims to test the application of the Discovery Learning model to improve the learning outcomes of eleventh-grade students of Light Vehicle Engineering (TKR) at SMK YPT Purworejo in the subject of Light Vehicle Electrical Maintenance (PKKR). The method used is Classroom Action Research (CAR) using the Kemmis and McTaggart model, which is implemented in two cycles, each including planning, action, observation, and reflection. The research subjects consisted of 34 eleventh-grade TKR students. Data were collected through observation of student activities, learning achievement tests, and documentation. Data analysis used a quantitative approach by calculating the average value and percentage of learning completion, supported by qualitative analysis to identify changes in student behavior during the learning process. The results of the study showed a gradual increase in student learning outcomes in each cycle. In the pre-cycle stage, only 10 of 34 students (29.41%) achieved the Minimum Competency (KKM) (80) with an average value of 74.58. In Cycle I, the number of students who completed the course increased to 23 (67.65%) with an average value of 80.88. Furthermore, in Cycle II, this number increased to 30 students (88.24%) with an average score of 85.73, exceeding the established success indicator of 75%. This finding indicates that the implementation of the Discovery Learning model is effective in improving the cognitive learning outcomes of 11th-grade TKR students at SMK YPT Purworejo in the Light Vehicle Electrical Maintenance competency.